Antipsychotic-related fatal poisoning, England and Wales, 1993–2013: impact of the withdrawal of thioridazine. (2nd July 2016) - Handley, S.; Patel, M. X.; Flanagan, R. J.
Abstract: Context : Use of second generation antipsychotics in England and Wales has increased in recent years whilst prescription of first generation antipsychotics has decreased.Methods : To evaluate the impact of this change and of the withdrawal of thioridazine in 2000 on antipsychotic-related fatal poisoning, we reviewed all such deaths in England and Wales 1993–2013 recorded on the Office for National Statistics drug poisoning deaths database. We also reviewed antipsychotic prescribing in the community, England and Wales, 2001–2013.Use of routine mortality data : When an antipsychotic was recorded with other drug(s), the death certificate does not normally say if the antipsychotic caused the death rather than the other substance(s). A second consideration concerns intent. A record of "undetermined intent" is likely to have been intentional self-poisoning, the evidence being insufficient to be certain that the individual intended to kill. A record of drug abuse/dependence, on the other hand, is likely to have been associated with an unintentional death.Accuracy of the diagnosis of poisoning : When investigating a death in someone prescribed antipsychotics, toxicological analysis of biological samples collected post-mortem is usually performed. However, prolonged attempts at resuscitation, or diffusion from tissues into blood as autolysis proceeds, may serve to alter the composition of blood sampled after death from that circulating at death. With chlorpromazine and with olanzapine a further factor is that these compounds are notoriously unstable in post-mortem blood.Deaths from antipsychotics : There were 1544 antipsychotic-related poisoning deaths. Deaths in males (N = 948) were almost twice those in females. For most antipsychotics, the proportion of deaths in which a specific antipsychotic featured either alone, or only with alcohol was 30–40%, but for clozapine (193 deaths) such mentions totalled 66%. For clozapine, the proportion of deaths attributed to either intentional self-harm, or undetermined intent was 44%, but for all other drugs except haloperidol (20 deaths) the proportion was 56% or more. The annual number of antipsychotic-related deaths increased from some 55 per year (1.0 per million population) between 1993 and 1998 to 74 (1.5 per million population) in 2000, and then after falling slightly in 2002 increased steadily to reach 109 (1.9 per million population) in 2013.Intent : The annual number of intentional and unascertained intent poisoning deaths remained relatively constant throughout the study period (1993: 35 deaths, 2013: 38 deaths) hence the increase in antipsychotic-related deaths since 2002 was almost entirely in unintentional poisoning involving second generation antipsychotics. Clozapine, olanzapine, and quetiapine were the second generation antipsychotics mentioned most frequently in unintentional poisonings (99, 136, and 99 deaths, respectively). Mentions of diamorphine/morphine and methadone (67 and 99 deaths, respectively) together with an antipsychotic were mainly (84 and 90%, respectively) in either unintentional or drug abuse-related deaths.Deaths and community prescriptions : Deaths involving antipsychotics (10 or more deaths) were in the range 11.3–17.1 deaths per million community prescriptions in England and Wales, 2001–2013. Almost all (96%) such deaths now involve second generation antipsychotics. This is keeping with the increase in annual numbers of prescriptions of these drugs overall (<1 million in 2000, 7 million in 2013), largely driven by increases in prescriptions for olanzapine and quetiapine. In contrast, deaths involving thioridazine declined markedly (from 40 in 2000 to 10 in 2003–2013) in line with the fall in prescriptions for thioridazine from 2001.Conclusions : The removal of thioridazine has had no apparent effect on the incidence of antipsychotic-related fatal poisoning in England and Wales. That such deaths have increased steadily since 2001 is in large part attributable to an increase in unintentional deaths related to (i) clozapine, and (ii) co-exposure to opioids, principally diamorphine and methadone.